Implementation Of The STEM Approach to Science Learning at MI Nurul Huda Sidokumpul Guntur Demak - Nailis Sarifah; M. Rofi Fauzi (PGMI IAIN Lhokseumawe, 2026)
Study This aim for describe implementation Science Technology Society (STEM) approach to science learning at MI Nurul Huda Sidokumpul, Guntur District, Demak Regency. In study at this time, STEM learning was implemented through activity experiment water hyacinth Hyacinth (Eichhornia crassipes) as a simple and easy observation medium understood participant educate Elementary Madrasah level. Participants educate observing two containers water hyacinth goiter for 5 days: Container A contains clean water and Container B contains water mixed with soap. Observation results show that water hyacinth goiter in Container B experienced wilting since day 2 and died completely on day 5, while water hyacinth goiter in Container A remains grow fertile. Research use method qualitative descriptive with technique data collection in the form of observation, interview in-depth, and documentation. Subject study is participant educate Class V. Research results show that implementation STM approach is implemented through five stages: (1) invitation, (2) exploration, (3) explanation and solution, (4) decision making action, and (5) strengthening concept. The implementation of this approach has been shown to increase enthusiasm, active student involvement, and environmental awareness. The main obstacles identified were limited laboratory facilities and a lack of relevant local references. This study concludes that the STM approach is effective in science learning in Islamic elementary schools if supported by careful planning and adequate teacher pedagogical competence.